1989
DOI: 10.1152/ajpcell.1989.256.2.c452
|View full text |Cite
|
Sign up to set email alerts
|

Cytosolic magnesium modulates calcium channel activity in mammalian ventricular cells

Abstract: The effect of cytosolic free Mg2+ concentration on the regulation of myocardial function was studied by dialyzing isolated guinea pig ventricular myocytes with different internal Mg2+ concentrations [( Mg2+]i). We found that elevation of [Mg2+]i shortened the action potential and suppressed the Ca2+ current. Mean values recorded for action potential duration in cells dialyzed with solutions containing 0, 1.3, and 9.4 mM Mg2+ were 620 +/- 40, 400 +/- 25, and 60 +/- 10, respectively. The suppressive effect of [M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
67
1

Year Published

1991
1991
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(78 citation statements)
references
References 16 publications
10
67
1
Order By: Relevance
“…2E). Augmentation of Ca 2+ current in low [Mg2+]i has also been reported in cardiac muscle cells [25]. One may still argue that tail currents may contribute to terminating caffeine-induced Ca 2+ release.…”
Section: Low [Mf+]i Abolishes Risc Over a Wide Range Of Depolarizing mentioning
confidence: 78%
“…2E). Augmentation of Ca 2+ current in low [Mg2+]i has also been reported in cardiac muscle cells [25]. One may still argue that tail currents may contribute to terminating caffeine-induced Ca 2+ release.…”
Section: Low [Mf+]i Abolishes Risc Over a Wide Range Of Depolarizing mentioning
confidence: 78%
“…Inhibition of calcium channel activity by [Mg2+]i has also been reported in guinea pig ventricular myocytes, though the mechanism differs in that it is independent of ligandmediated phosphorylation (Agus et al, 1989 (Maguire, 1984;Romani & Scarpa, 1990 In summary, therefore, elevation of serum magnesium to 1.5-2.0 mm has little effect on normal cardiac electrophysiology but has been reported to reduce the frequency of clinically significant arrhythmias early after acute myocardial infarction in several controlled trials. Laboratory studies suggest that magnesium may have an anti-arrhythmic action by suppressing automaticity in partially depolarized cells and that inhibition of calcium current is likely to contribute to this effect.…”
Section: Electrophysiological and Antiarrhythmic Effects Of Magnesiummentioning
confidence: 95%
“…Cukierman et al (1988) reported a 7-14 mV hyperpolarizing shift for sodium channels in response to 7-5 mm inside Ca2 . Hartzell & White reported a 10 mV hyperpolarizing shift of calcium channel activation in response to an increase from 0 3 to 3 mm inside Mg2+, although Agus et al (1989) failed to see a shift of calcium channel availability by 9-4 mm inside Mg2+. Our results support the conclusion of Hartzell & White (1989) that fixed negative charges exist on the inside of the calcium channel.…”
Section: Effect Of Inside Mg2+ On Ca2+ Channelsmentioning
confidence: 98%